Study on extraction of pandan flavor from pandan leaves using steam distillation - Erna Qurratu' Aini, Ruslan (2011)
Pandan is one of the leaves that contain the essence inside and release the key aroma component as their heating with the boiling point of water. The aroma compound itself is very useful for the industrial flavorings in Southeast Asia. The objective of this research is to determine the best operating parameter for the extraction of Pandan flavor from Pandan leaves using steam distillation. The parameter of the operating is varied which is the time; temperature and also the ratio of distill water with pandan leaves. Pretreatment also been done in order to get higher removal of natural flavor from pandan leaves. The pandan compound is analyzed by using GC FID to find one of key aroma compound which is 3-hexanol by using the 3-hexanol standard curve as references. The result shown, the yield of the oil that get mostly is proportional with the concentration of 3-hexanol as one of the compound in pandan. The best condition is to get purified pandan flavor is at the 6 hours with the temperature 100°C at ratio 1:6. The study is economically feasible and it is proven to be favorable as increasing the quality of the pandan flavorings compared to the industrial. The method also that be used is suitable as using steam distillation as the extraction process which is more safe and reliable.